Efeito da amplitude da dieta e da abundância de plantas sobre o uso de hospedeiras por insetos herbívoros em capítulos de asteraceae - Nobre, Paola Arielle Ferreira (2015)
the factors that influence the choice of egg-laying sites by adult insects is critical in order to identify the major drivers of host-plant use by insects. The abundance of different plant species and the level of feeding specialization of insects have been considered as determinants of the preferential use of host-plants by herbivorous insects. We analyzed the host use patterns of endophagous insects that feed on Asteraceae flower-heads to test the following hypotheses: (i) the abundance of a plant species has a positive effect on the preference of herbivorous insects for that plant species, and (ii) the relative importance of plant abundance in determining preferential use is greater for herbivorous species that use a wider range of host-plant species. We used data on the interactions between herbivorous insects and Asteraceae host-plants family sampled in 20 Cerrado areas in São Paulo State. We analyzed 11 species of endophagous insects and 12 host-plant species. For eight species of herbivorous insects, plant species abundance showed a positive influence on herbivore preference. Three insect species did not respond to any influence of plant abundance on feeding preferences, but one of them showed a positive effect of plant species identity. Furthermore, both the most specialized and the most generalist insect species presented a stronger positive effect of plant species abundance in their choice of a host-plant. Therefore, our study shows that the abundance of plant species is a major factor determining the preferential use of hostplants by the endophagous insects of Asteraceae. Moreover, we show that herbivore diet breadth mediates the relationship between host use and plant abundance.